2015
DOI: 10.1111/tbed.12440
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza H5N1 Surveillance and its Dynamics in Poultry in Live Bird Markets, Egypt

Abstract: H5N1, a highly pathogenic avian influenza (H5N1 HPAI), is an endemic disease that is significant for public health in Egypt. Live bird markets (LBMs) are widespread in Egypt and play an important role in HPAI disease dynamics. The aim of the study was to evaluate the H5N1 HPAI prevalence in representative LBMs from 2009 to 2014, assess the effects of other variables and evaluate past outbreaks and human cases. It was found that ducks and geese are high-risk species and that the prevalence of H5N1 HPAI was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…26 The LBMs surrounding Phnom Penh have been established as foci for poultry movement in the country 18,27 and a previous market surveillance study in 2011 revealed a high rate of influenza A/H5N1 circulation in this setting. 25 To our knowledge, AIVs were detected in Cambodian LBMs during 2013 at a higher frequency than any other study published previously, 25,[28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 52%
“…26 The LBMs surrounding Phnom Penh have been established as foci for poultry movement in the country 18,27 and a previous market surveillance study in 2011 revealed a high rate of influenza A/H5N1 circulation in this setting. 25 To our knowledge, AIVs were detected in Cambodian LBMs during 2013 at a higher frequency than any other study published previously, 25,[28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 52%
“…It has also been reported that the virus survival time in the cold environment is enhanced (Paek et al, 2010;Kurmi et al, 2013). Previous reports claim that subtype H5N1 infections in poultry are associated with poultry densities and has been highly correlated with crop production (Bodbyl-Roels et al, 2011;Fuller et al, 2013;El-Masry et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The majority (approximately 81% of the broilers, 64% of the layers, 79% of the ducks and 39% of the turkey farms) are from Lower Egypt, while Middle Egypt (Cairo and Giza) represents the second largest (13, 29, 14 and 49%, respectively). The remainder of commercial farms are found in Upper Egypt (Jones, 2008).The backyard breeding and meat production (Sector four) often called the household poultry plays a key role the H5N1 dynamic in poultry in Egypt and have been shown to play significant roles in human and poultry infections (Abdel-Moneim et al, 2009;Abdelwhab and Hafez, 2011;El-Masry et al, 2015). This sector is characterized by randomly dispersed, small-sized, individually-owned household flocks that usually are raised as mixed bird species of different ages in Egypt (Fasina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The highest numbers of outbreaks have been recorded in Dakahliya, Monofiya, Kalyobiya, Sharqeia, Gharbia, and Giza Governor-ates, which are leading poultry-producing governorates in Egypt ( Fig. 2A; El-Zoghby et al 2013;Kayali et al 2016;ElMasry et al 2017;EMPRES 2019).…”
Section: Emergence and Epidemiology Of A(h5n1) Viruses In Egyptmentioning
confidence: 99%